PENGARUH ROA, LEVERAGE, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Vidya Vitta Adhivinna (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
This research aims to analyze and obtain empirical evidence about the effects of Return On Asset (ROA), leverage, institutional ownership and firm size to tax avoidance. The independent variables use are Return On Asset (ROA), leverage, institutional ownership and firm size. The dependent variable is tax avoidance.The research population was manufacturing companies listed in Indonesia Stock Exchange during 2011-2015 period. Sample was collected by purposive sampling method. Total 56 manufacturing companies were taken as studies sample. Analysis method of this research used multiple regression.The result of this research showed that Return On Asset (ROA) has an effect on tax avoidance with a significance value of 0,000, leverage has no effect on tax avoidance with a significance value of 0,292, institutional ownership has no effect on tax avoidance with a significance value of 0,224 and firm size has no effect on tax avoidance with a significance value of 0,065.